2022
DOI: 10.1155/2022/9281636
|View full text |Cite|
|
Sign up to set email alerts
|

The Diagnostic Value of Serum GDF15 and hs-CTnT in Elderly Patients with Acute Myocardial Infarction

Abstract: Objective. To analyze the diagnostic value of serum growth differentiation factor 15 (GDFl5) and high-sensitivity troponin T (hs-cTnT) in elderly acute myocardial infarction (AMI). Methods. A retrospective analysis of 165 patients with acute chest pain admitted to the Department of Cardiology in our hospital from January to December 2020, Among them, 76 AMI patients (AMI group), 89 non-AMI patients (non-AMI group), and 80 healthy people were selected as the control group during the same period. Compare the thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%